Respon Mahasiswa Terhadap Keberadaan Galeri Investasi Bursa Efek Indonesia di Universitas Pendidikan Ganesha - Riastuti, Ni Kadek; Sujana, I Nyoman (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
This study aimed to determine the response of the Economic Faculty students to the existence of the Indonesia Stock Exchange investment gallery at the Ganesha University of Education. The type of research was a descriptive study with a quantitative approach to describe the responses of Economic Faculty students to the existence of the Indonesia Stock Exchange investment gallery at the Ganesha University of Education. Data collection methods were using questionnaires.The population of this study were 2.637student of the economic faculty with 347 respondent as the sample that determined by the slovin formula. The data was analyzed descriptively. Based on the results of the study, students’ responses to the perception indicators obtained a score of 2.351, included in not a good category. The attitude indicator obtained a score of 2.534, included in the less good category. The participation indicator obtained a score of 2.435, included in the unfavorable category.